War and peace - Pulman, Jack; Tolstoy, Leo, graf, 1828-1910 ([S.l.] : British Broadcasting Corporation)
Summary: A dramatisation of Tolstoy's towering historical panorama, an epic of love and hate, power and passion, war and peace. It also the story of two Russian families, the Rostovs and the Bolkonskys, inexorably interlinked during the turbulent years of Napoleonic wars.
Copy available in DVD format
Cast : Anthony Hopkins, Rupert Danes, faith Brook, Morag Hood
Keywords: Motion pictures; Historical films